Inmate carrier of cutis verticis gyrata - PA Martínez-Carpio; M Formigón Roig; S Matas Marín; A Aranda Sánchez; A Bedoya del Campillo (Sociedad Española de Sanidad Penitenciaria, 2019)
Abstract The cutis verticis gyrata (CVG) is a clinical stigma considered to be very rare that mostly affects males. It consists of characteristic folds in the scalp, similar to cerebral convolutions, which tend to affect the parietal and occipital areas. It is considered a pachyderma of the cranial skin, and can appear at different ages for different reasons. Images are shown of the first clinical case described in prisons, as well as the initial diagnostic and therapeutic approach.